Analisis Manajemen Sarana Prasarana dan Sumber Daya Pendidikan dI SMAN 1 Tanjungsari Kabupaten Bogor - Hidayat, Cecep; Iskandar, Iskandar; Ratno, Ade; Pipih, Pipih; Yusro, M. Awaluddin; Nandani, Dhea (Jaanur Elbarik Indonesia, 2026)
This study aims to analyze the management of facilities, infrastructure, and educational resources at SMAN 1 Tanjungsari, Bogor Regency. The research was conducted through field observations during the School Field Introduction Program implemented over 24 working days from January 14 to February 16, 2026. The results indicate that SMAN 1 Tanjungsari faces several significant challenges in educational management, including shortage of classrooms to accommodate the increasing number of students, limited teaching staff, and absence of school fencing that impacts student conditioning difficulties, especially during entry and break times. As the only public senior high school in Tanjungsari District, the school experiences high public demand that is disproportionate to its available capacity. This study recommends the need for infrastructure improvement through additional study groups, teacher recruitment, and supporting infrastructure development to enhance educational service quality.